Effects of changes in salinity on oxygen and food consumption of the young sub-Antarctic notothenioid Eleginops maclovinus: possible implications of their use of an estuarine habitat - Vanella, Fabián Alberto (2016)
Salinity is one of the most important structuring factors in the distribution and bioenergetics of estuarine fishes. The aims of this work were to study the distribution of the sub-Antarctic, eurythermic, euryhaline and coastal notothenioid Eleginops maclovinus in Lapataia estuary (Tierra del Fuego National Park), in relation to salinity conditions, and the effect of salinity on the oxygen con- sumption of this species. The spread of the mixing zone of Lapataia was studied and physicochemical properties (conductivity, pH, temperature and salinity) were mea- sured. Distribution of E. maclovinus juveniles was inves- tigated principally by electrofishing in the field. Oxygen consumption of absorptive and post-absorptive young-of- the-year individuals (8?10 cm total length) was analyzed by stop-flow respirometry measurements, performed at three salinities (1, 12 and 30 psu). The intermediate mixing zone is relatively small in this system, showing an exten- sion of *1.5 km upstream from Lapataia Bay. It was found that there was a strong relationship between the mixing zone and the distribution of juveniles of E. maclovinus. No differences were found in the metabolic baseline at different salinities. A punctual feeding provoked a typical SDA response, with a significant higher ingested food and metabolic scope at intermediate salinity (12 psu). An increased scope was reached by increasing the energy intake and not through a decrease in the standard metabolic rate. Under an available food condition, this capacity could result in an increased growth rate at inter- mediate salinity.